P635 Real-world treatment persistence and associated costs with biologic therapy in patients with inflammatory bowel disease (IBD): Results of a retrospective cohort analysis of 1, 149 patients treated in Germany. (16th January 2018) - Groth, A; Wilke, T; Brandes, A; Ratsch, B; Fuchs, A; Deiters, B; Bokemeyer, B
Abstract: Background: Data on biologic treatment (Tx) persistence and switching in German IBD patients are sparse. The main objectives of this interim analysis of a retrospective claims database (7.5 Mio. insured, covering out- and inpatient care) were to describe rates of biologic Tx switching and discontinuation for anti-TNFα (adalimumab, golimumab, infliximab) and vedolizumab (VDZ) IBD patients and to report associated drug costs. Methods: Adult patients with a confirmed diagnosis of Crohn's disease or ulcerative colitis (63% of 37%), initiating Tx with an anti-TNFα or VDZ between 1 July 2015 and 30 June 2016 and follow-up for 12 months (or death within 12 months) were included. Observation started with the first prescription in this period. First observed Tx discontinuation (prescription gap >90 days) and switching to another biologic were compared between anti-TNFα and VDZ patients, both unadjusted and adjusted (Cox regression). Drug costs, based on pharmacy retail prices, were reported per observed patient month for periods of continuous index Tx. Results: 1149 out of 51, 222 IBD patients started anti-TNFα or VDZ within the inclusion period. Of these, 582 patients were followed up for 12 months or until death ( n = 4) in this interim analysis (476 anti-TNFα: mean age, 37.2 years, 53.9% female, 78.7% bio-naïve; 107 VDZ: mean age, 40.5 years, 55.1% female, 21.5% bio-naïve). During follow-up, 20.6% vs. 16.8% of anti-TNFα vs. VDZ patients ( p = 0.227) switched to another biologic agent; 19.8% vs. 15.0% ( p = 0.154) discontinued index Tx, and 59.4% vs. 67.6% (five patients censored; p = 0.060) continued Tx. VDZ Tx was associated with longer drug survival (mean 309 days) than anti-TNFα Tx (286 days; p = 0.028). In the multivariable Cox regression, female gender was associated with earlier Tx discontinuation and switch (HR = 1.490; 95% CI: 1.139–1.949), whereas VDZ Tx was associated with later discontinuation and switch (HR = 0.692; 95% confidence interval (CI): 0.480–0.998); prior biologic Tx and comorbidity were not significant. Drug costs per patient month were €2, 561.66 for anti-TNFα and €2, 314.74 for VDZ. Conclusions: In contrast to previous observational evidence, less than two-thirds of IBD patients continued Tx with a biologic agent after 12 months. There is a tendency towards a longer drug survival in VDZ patients, with comparable drug costs. Analysis of the full dataset including 1, 149 patients will provide more detail, especially for subgroups (UC vs. CD and bio-naïve vs. bio-experienced).